(untitled) (Cultura Económica, 2019)
Analyzing the decades of persistent poverty and inequity in Latin America, the authors show that the roots of the problem can be found in failures of the economic theory that supports public policies applied in the region. Hence the challenge of rebuilding the theoretical structure of Economics. As a more integrated approach to meet such a big challenge, the rediscovered concept of Human Economy, within the framework of a Harmonious Human Development offers a more comprehensive approach. These are L. J. Lebret’s concepts. He understood the Human Economy as, “a discipline of thought and action oriented towards an authentic development, well rounded, of each man and of the whole man, to move from a less human stage, to a more human condition” (Lebret, 1966:32). From this perspective Economic Science becomes a new science of synthesis, interdisciplinary and with an ethical ground. It would be an optimal way to overcome the epistemological and methodological failures of “Mainstream Economics”. It would generate a friendly relatioship between Humanity and Nature, pointing to a universal ascent of men and women alike. The article ends highlighting some elements of solidarity and humanizing goals that can be found in some other economic conceptions, critical of the Mainstream.